Method of fluorescence polarization for a new alternative tool for investigation of cooking oil and lard. (May 2019) - Azam, M; Afiefah, I; Septianti, R W; Putri, N K; Sugito, H; Firdausi, K S
Abstract: Testing the quality of cooking oil is very important, especially to ensure the quality and identification of other unexpected mixture of cooking oil. In this paper, the fluorescence polarisation method will be used to test the presence of lard contamination on cooking oil. Fluorescence polarization is similar to fluorescence intensity, in that it is based on the emission of light by an excited fluorophore. However, samples are excited by polarized light which is selected by specific polarizing filters. The angle of linearly polarized incoming light was adjusted by using a polarizer. The change of fluorescent polarization angle was measured by using a second polarizer (analyzer) to obtain a relation between θ-value and φ-value for all samples. The samples were various edible oils, i.e., chicken oil, lard, and canola oil. The test is carried out by measuring the change in the average polarization angle of the fluorescent light to the polarizing angle of each incoming light over the sample directly. The results of the critical angle showed that all three samples were characteristic. Chicken oil has φc = 20° with θAv = 11.28° to 13.63°, lard has φc = 40° with θAv = 7.13° to 9.51°, whereas canola oil has φc = 30° with θAv = 2.59°. These results show that the fluorescence polarization method has a good prospect for oil contamination test on cooking oil.